2017
DOI: 10.1007/s00280-017-3496-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the ABCB1 polymorphisms on the response to Taxane-containing chemotherapy: a systematic review and meta-analysis

Abstract: This study highlights the unsuitability of relying on the ABCB1 rs1045642 and rs1128503 polymorphisms as therapeutic response biomarkers of Taxane-containing chemotherapy. Further polycentric studies in larger and multiracial populations are needed to validate the conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This finding is consistent with the results of two previous multicenter studies conducted in the United States and Japan. A meta-analysis reported by Jiang et al, (2018) revealed that the rs1045642 and rs1128503 polymorphisms were not related to the response to chemotherapy. Although heterogeneities were found in the overall analyses of PFS and OS in the C3435T homozygote and dominant models, subgroup analysis identified geographical area, tumor type, and chemotherapy regimen as the three main sources of heterogeneity between studies.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the results of two previous multicenter studies conducted in the United States and Japan. A meta-analysis reported by Jiang et al, (2018) revealed that the rs1045642 and rs1128503 polymorphisms were not related to the response to chemotherapy. Although heterogeneities were found in the overall analyses of PFS and OS in the C3435T homozygote and dominant models, subgroup analysis identified geographical area, tumor type, and chemotherapy regimen as the three main sources of heterogeneity between studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of two previous multicenter studies in the United States and Japan. A metaanalysis reported by Jiang revealed that the rs1045642 and rs1128503 polymorphisms were not related to the response to chemotherapy [37]. Although heterogeneities were found in the overall analyses of PFS and OS in the C3435T homozygote and dominant models, we conducted subgroup analysis and identified the geographical area, tumor type, and chemotherapy regimen as the three main sources of heterogeneity between studies.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note that a high expression of ABCB1 in tumor cells is associated with poor prognosis and the development of multidrug resistance in a way that makes them attractive prognostic markers with high clinical impact in different types of cancer in adults [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%